Faktor yang berhubungan dengan Pelaksanaan Gerakan Ketuk Pintu di Puskesmas Arcamanik - Gita Komara; Asri Handayani Solihin; Yeni Suryamah (Sehat MasadaJurnal, 2019)
Arcamanik Community Health Centre launched a program namely “gerakan ketuk pintu” by the cadres of Tuberculosis (TB) in a bid to improve the control of TB disease. Based on the upshot in March 2017 had no significant impact on the coverage due to several factors that can be conttributed such as the knowledge, attitude, motivation, and working period of TB cadres. Therefore, this research aimed to determine which factors that related to the implementation of the gerakan ketuk pintu in Arcamanik Health Centre Care through correlation descriptive type with cross-sectional approach. The sample is 31 people. In this research, Questionnaires and standard operating procedures (SOP) lists were used as an instrument. Data analysis using Chi Square Test. The results that factors related to the implementation of “gerakan ketuk pintu” is motivation (p=0,005), attitude (p=0,02),and knowledge (p=0,031) and not correlated with working time period (p=1,000). From this results, Arcamanik Community Health Centre are expected to aid the roles of cadres within the “gerakan ketuk pintu” through the health education and training periodically, conducting a counseling and budgetary planning to support the implemented program